Academic supervisor leadership and its influencing mechanism on postgraduate creativity in China. (September 2018) - Meng, Yi; Zhao, Congjian
Abstract: Based on Amabile's componential theory of creativity, this study hypothesized and tested a mediating model in which academic supervisor leadership (ASL) influenced postgraduate creativity through intrinsic motivation, creative thinking, and professional knowledge. A total of 815 postgraduates from four universities were selected through stratified cluster sampling to complete questionnaires. Of the 697 responses, 677 were valid, yielding a response rate of 83.06%. Structural equation modeling (SEM) was employed to analyze the data, and the results supported all hypotheses. The findings were that ASL could be referred to as a process in which academic supervisors construct, protect, and develop students' creativity through empowering, considering, motivating, and developing behaviors; ASL positively influenced postgraduate creativity through intrinsic motivation, creative thinking, and professional knowledge; these mediating variables were interactional, intrinsic motivation promoting creative thinking and professional knowledge, and professional knowledge underlying creative thinking. This study confirmed the operational conception of ASL and verified the componential theory of creativity in response to the call for more in-depth studies on the motivational mechanisms of creativity. The practical implications of academic supervisors' leadership practices and universities' creativity management are discussed.